Reincarnation of the Pinay Subaltern in Foreign Cinema - Yu, Taeyun (Archīum Ateneo, 2024)
This paper explores the paradoxical condition of postcolonial practice in South Korea1 that is, in many ways, complicit with dominant discourses such as nationalism, patriarchy, and global capitalism. In such a condition, what remains obscured is the voice of women that behooves us to hypothesize that the image of diasporic Filipino women in Korean cinema is predetermined by such complicity and is ideologically reincarnated as the subaltern. By conflating two postcolonial concepts, hybridity (Bhabha) and subalternity (Spivak), the study inspects the hypothesis through an analysis of two films that depict diasporic Pinay images: as entertainer in Yangil Choi’s All Under the Moon (1993) and as migrant wife in Han Lee’s Wandeugi (a.k.a. Punch, 2011). In so doing, this paper revisits Spivak’s ethical question “Can the subaltern speak?” in the postcolonial feminist context.